De/constructing Literacies: Considerations for Engagement - Lemieux, Amélie (Peter Lang, 2020)
De/constructing Literacies: Considerations for Engagement reviews and defines the concept of engagement in literacy studies from different epistemologies. Well-suited for literacy researchers and graduate students, it considers the foundations of arts-based research, cognitive psychology, ethnography, phenomenology, posthumanism, with a final chapter on walking methodologies, to better understand how engagement can be framed and looked at in literacy studies.

“Back then it was only men who worked in these kind of fields”: Observing little sparks through the prism of affect and gender in maker literacies research. - Lemieux, Amélie (Reading Research Quarterly, 2023)

Porosité et didactique de la littérature au secondaire : Didactisation d’une oeuvre théâtrale et de son adaptation filmique pour un réinvestissement poétique en classe de français - Lemieux, Amélie (La Lettre de l’AIRDF, 2023)

Pour une lecture émancipatoire : bell hooks - Lemieux, Amélie (Revue des sciences de l'éducation, 2022)

M/EDIA/tions: Assises théoriques relatives aux questions d’équité, de diversité, d’inclusion et d’accessibilité (EDIA) pour l’enseignement de la littérature avec le numérique - Lemieux, Amélie (Revue de recherches en littératie médiatique multimodale, 2021)

Antidualisms in maker literacies research: Technological processes, materialities, mappings - Lemieux, Amélie (Education & Didactique, 2021)

What does making produce? Posthuman insights into documenting relationalities in maker education for teachers - Lemieux, Amélie (Professional Development in Education, 2021)

Vers une documentation d'oeuvres littéraires numériques queer - Lescouet, Emmanuelle; Vallières, Amélie; Lemieux, Amélie (BD, Littératie et créations numériques : Quels enjeux pour demain?, 2023)

Sur la notion d’engagement envers la lecture : Constats, angles morts et complexités - Lemieux, Amélie; Berthiaume, R. (Nexus, 2023)

Éclosions in literacy research: Rereading Brandt and Clinton's “Limits of the local” - Ferguson, D.; Lemieux, Amélie (Journal of Literacy Research, 2022)

When in doubt, map it out: Teachers’ digital storytelling researched through documentation - Lemieux, Amélie; Mason, S. (Canadian Journal of Learning and Technology, 2022)

W(e)aving: When maker literacies and diffraction collide - Lemieux, Amélie; Thériault, V. (Studies in the Education of Adults, 2021)

On the relational autonomy of materials: Entanglements in maker literacies research - Lemieux, Amélie; Rowsell, Jennifer (Literacy, 2020)

Dis/comforting shelfies: Travelling literacies other-wise in disrupted times. - Scott, F.; Lemieux, Amélie; Johnston, K (Digital Culture & Education, 2022)

À l’aube de la transmédialité : de l’oeuvre antérieure comme péritexte - Lemieux, Amélie (Péritexte et transmédialité, 2023)

Working towards more socially just futures: Five areas for transdisciplinary literacies research - Lemieux, Amélie; Boyle, L.; Simmonds, E.; Rahm, J. (Literacy, 2023)

Visualizing mapping as pedagogy for literacy futures - Lemieux, Amélie; Smith, A.; McLean, C.; Rowsell, Jennifer (Journal of Curriculum Theorizing, 2020)

Crafting stories and cracking codes in a Canadian elementary school - Lemieux, Amélie; Rowsell, Jennifer (Maker Literacies and Maker Identities in the Digital Age: Learning and Playing through Modes and Media, 2021)

Maker research: A proposition of thinking-with maker culture as slow scholarship - Sinner, A.; Lemieux, Amélie (Connection-Contact-Community, 2021)

Intra-active entanglements: What posthuman and new materialist frameworks can offer the learning sciences - Sheridan, M. P.; Lemieux, Amélie; Do Nascimento, A.; Arnseth, H. C. (British Journal of Educational Technology, 2020)

Defining artful literacies : Adolescent affects, belonging and cross-sectorial creativity - Lemieux, Amélie; Beaton, E. (Art Education in Canadian Museums: Practices in Action, 2024)

‘This Documentary Actually Makes Welland Look Good’: Exploring Posthumanism in a High School Documentary Film Project - Lemieux, Amélie; Rowsell, Jennifer (Transforming Language and Literacy Education: New Materialism, Posthumanism, and Ontoethics, 2020)

18e séminaire de recherche en littératie médiatique multimodale | LMM - Brunel, Magali; Boutin, Jean-Francois; Coste, Jimmy; Lalonde, Martin; Lemieux, Amélie; Audet, René (2021)

InstaPoésie : de l’espace de partage littéraire virtuel à la production de textes poétiques en classe du secondaire - Lemieux, Amélie; Barton, G.; Lewkowich, D.; White, B.; Gauthier, M.-C.; Beauchamp, F. (Revue de recherches en littératie médiatique multimodale, 2022)

Diff/reading data through pedagogies of the other-wise - Lemieux, Amélie; Johnston, K; Scott, F. (Unsettling Literacies: Directions for Literacy Research in Precarious Times, 2022)

Taking a wide-angled view of contemporary digital literacy - Lemieux, Amélie; Rowsell, Jennifer (The Routledge Handbook of Digital Literacies in Early Childhood, 2020)

On recruiting aesthetic experience: A trioethnography of the affordances and limitations of teaching (with) the arts and literature in a pandemic year - White, B.; Lemieux, Amélie; Émond, Anne-Marie (Making Connections in and through Arts-based Educational Research, 2023)

Éduquer à la littératie numérique: communication, culture et création. - Lacelle, Nathalie; Acerra, Eleonora; Audet, René; Boutin, Jean-Francois; Brehm, Sylvain; Gervais, Bertrand; Lalonde, Martin; Mercier, Jean-Pierre; Martel, Virginie; Richard, Moniques; Lemieux, Amélie; Guichon, Nicolas; et al. (Fonds de Recherche du Québec - Société et culture, 2020)

20e séminaire en LMM ... sortez vos paillettes! | LMM - Boutin, Jean-Francois; Amélie Lemieux; Blanchette, Karine; Lalonde, Martin; Vallières, Amélie; Dumoulin, Pierre-Gabriel; Mahieu, Luc; Gladu, Eve; Martel, Virginie; Lacelle, Nathalie; Audet, René; Lahouste, Corentin; et al. (2022)